Non-invasive specimen collections for Mycobacterium tuberculosis detection in free-ranging long-tailed macaques (Macaca fascicularis) - Suthirote Meesawat; Nalina Aiempichitkijkarn; Saradee Warit; Mutchamon Kaewparuehaschai; Suchinda Malaivijitnond (PLoS ONE, 2023)
Surveillance of infectious diseases in free-ranging or wild animals has been widely conducted in many habitat-range countries after the COVID-19 episode. Thailand is located in the center of the distribution range of long-tailed macaques (Macaca fascicularis; Mf) where the animals have both frequent human contact and a high prevalence of human tuberculosis. For the large-scale detection of Mycobacterium tuberculosis complex (MTBC) using IS6110-nested PCR in free-ranging Mf, non-invasive sampling was developed using oral (via rope bait) and fecal (direct swabs of fresh feces) specimen collection. Firstly, the MTBC-IS6110-nested PCR was validated in non-invasively collected specimens, in terms of its specificity and sensitivity, and then compared with those of the invasively collected oral and rectal swabs in 24 captive MTBC-suspected Mf. After validation, these methods were applied to survey for the prevalence of shed MTBC (MTBCS) in four previously reported MTBC-infected populations. A total of 173 baited rope specimens and 204 freshly defecated excretions were collected. The limit of detection of the IS6110-nested PCR technique was 10 fg/μL and the 181-bp PCR amplicon showed 100% sequence similarity with the MTB H37Rv genome sequence. Comparing the MTBCS detection between the invasive and non-invasive collected specimens in captive suspected Mf revealed a significant correlation between the two types of oral specimens (oral swabs and baited ropes; n = 24, r2 = 1, p-value < 0.001), but fresh fecal swabs showed higher MTBCS frequencies than the rectal swabs. Moreover, the proportion of MTBCS-positive free-ranging Mf were significantly higher in the fresh fecal swabs (8.82%; 95% CI; 4.9–12.7%) than in the baited ropes (5.20%; 95% CI; 1.9–8.5%). This result indicates that oral sampling via baited ropes and fecal sampling via defecated excretion swabs can serve as ancillary specimens for MTBCS detection in free-ranging non-human primates.